2004
DOI: 10.1086/422916
|View full text |Cite
|
Sign up to set email alerts
|

The RR Lyrae Period‐Luminosity Relation. I. Theoretical Calibration

Abstract: We present a theoretical calibration of the RR Lyrae period-luminosity (PL) relation in the U BV RIJHK Johnsons-Cousins-Glass system. Our theoretical work is based on calculations of synthetic horizontal branches (HBs) for several different metallicities, fully taking into account evolutionary effects besides the effect of chemical composition. Extensive tabulations of our results are provided, including convenient analytical formulae for the calculation of the coefficients of the periodluminosity relation in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
461
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(513 citation statements)
references
References 24 publications
48
461
3
1
Order By: Relevance
“…and both the metal-rich and metal-poor extremes are represented by only two stars. Although our results are very similar to those obtained by Bono et al (2003), Catelan et al (2004), and Sollima et al (2008), we cannot reach firm conclusions concerning the metallicity dependence of the period-luminosity relation in the J band based solely on these data. Therefore, to increase the sample size, we added the Sollima et al (2006a) dataset for ω Cen (Fig.…”
Section: Period-[fe/h] Relationssupporting
confidence: 54%
See 2 more Smart Citations
“…and both the metal-rich and metal-poor extremes are represented by only two stars. Although our results are very similar to those obtained by Bono et al (2003), Catelan et al (2004), and Sollima et al (2008), we cannot reach firm conclusions concerning the metallicity dependence of the period-luminosity relation in the J band based solely on these data. Therefore, to increase the sample size, we added the Sollima et al (2006a) dataset for ω Cen (Fig.…”
Section: Period-[fe/h] Relationssupporting
confidence: 54%
“…To evaluate the latter, we proceeded as follows: The theoretical value of the blue edge of the RR Lyrae instability strip is located near T eff = 7200 K, whereas the red edge is near 6100 K (e.g., Smith 1995;Catelan 2004, and references therein). To transform these temperature values into near-IR colors, we can use the model calculations from Catelan et al (2004), where the RR Lyrae period-luminosity relation was studied using synthetic horizontal branch models. The corresponding relationship between near-IR temperatures and colors, as implied by those models, is given in Fig.…”
Section: Mean J and K S Magnitudes And Error Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies found that the metalpoor part of this relation was less steep (nearly flat according to McNamara) than the metal-rich part. Alternatively, a quadratic relation between M V (ZAHB) and metallicity was supported by several HB stellar evolution models (Dorman 1992;Cassisi et al 1999;VandenBerg et al 2000;Catelan et al 2004;Pietrinferni et al 2006) and pulsation models (Bono et al 2007), and was confirmed by empirical HB data for 61 Galactic GCs (Ferraro et al 1999).…”
Section: From Evolution and Pulsation Modelsmentioning
confidence: 78%
“…RR Lyrae stars make useful distance indicators because of the existence of an absolute magnitude-metallicity relation in the V band: (Sandage 1981a,b) and of a period-luminosity-metallicity relation in the K band: P L K Z (Longmore et al 1986, Bono et al 2003, Catelan et al 2004, Sollima et al 2008, and references therein).…”
Section: V − [Fe/h] and P L K Z Relations Of Rr Lyrae Starsmentioning
confidence: 99%